Comparing the magnitude and direction of asymmetry during the squat, countermovement and drop jump tests in elite youth female soccer players - Bishop, C.; Pereira, L. A.; Reis, V. P.; Read, P.; Turner, A. N.; Loturco, I. (Journal of Sports Sciences, 2020)
The aims of the present study were to provide an in-depth comparison of inter-limb asymmetry and determine how consistently asymmetry favours the same limb during different vertical jump tests. Eighteen elite female under-17 soccer players conducted unilateral squat jumps (SJ), countermovement jumps (CMJ) and drop jumps (DJ) on a portable force platform, with jump height, peak force, concentric impulse and peak power as common metrics across tests. For the magnitude of asymmetry, concentric impulse was significantly greater during the SJ test compared to CMJ (p = 0.019) and DJ (p = 0.003). No other significant differences in magnitude were present. For the direction of asymmetry, Kappa coefficients revealed fair to substantial levels of agreement between the SJ and CMJ (Kappa = 0.35 to 0.61) tests, but only slight to fair levels of agreement between the SJ and DJ (Kappa = -0.26 to 0.18) and CMJ and DJ (Kappa = -0.13 to 0.26) tests. These results highlight that the mean asymmetry value may be a poor indicator of true variability of between-limb differences in healthy athletes. The direction of asymmetry may provide a useful monitoring tool for practitioners in healthy athletes, when no obvious between-limb deficit exists.